Arecaceae potential for production of monofloral bee pollen. Issue 4 (4th July 2017) - de França Alves, Rodolfo; de Assis Ribeiro dos Santos, Francisco
Abstract: Bees often collect pollen from plants that are near their colonies or apiaries. Arecaceae are characterised by having species that flower throughout the year and produce large quantities of pollen. Pollen grains of Arecaceae have two main forms, namely monosulcate and trichotomosulcate. The study area is located in the coastal region of the state of Sergipe, Brazil, where large amounts of bee pollen are produced by Apis mellifera . This study aims to evaluate how Arecaceae contribute to the production of monofloral bee pollen. Samples of bee pollen loads were collected each month for two years (totalling 24 samples), acetolysed, and mounted on permanent slides. At least 500 grains of pollen were counted for each sample, the data was analysed, and figures were made using the Tilia software. The pollen grains of Cocos nucifera were present in 23 samples (96%), and concentrations of this pollen type varied between 1.1 and 46.8% (but were commonly above 20%). The concentration of Arecaceae pollen grains is the result of the large-scale production of coconuts along the coastline. However, the presence of other pollen types, such as Mimosa arenosa, Mimosa pudica, Mikania and Myrcia, compliments the diets of bees in the region. The results show that even when in low frequency, Cocos nucifera pollen grains represent a large proportion of pollen content compared with other pollen types, because of the large size of Arecaceae pollen grains.